2006
DOI: 10.1542/peds.2005-2299
|View full text |Cite
|
Sign up to set email alerts
|

Pheochromocytoma and Paraganglioma in Children: A Review of Medical and Surgical Management at a Tertiary Care Center

Abstract: The incidence of malignant pheochromocytoma/paraganglioma was high in children (47%), particularly those with apparently sporadic disease, paraganglioma, and tumor diameters of > 6 cm. Patients with a known genetic mutation or familial pheochromocytoma/paraganglioma were more likely to achieve resection with negative microscopic margins and had improved disease-specific mortality rates. Surgical resection remains the treatment of choice for pheochromocytoma and paraganglioma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
134
0
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 150 publications
(138 citation statements)
references
References 36 publications
2
134
0
2
Order By: Relevance
“…Children usually suffer from symptomatic and potentially life-threatening occurrence with bilateral and extraadrenal tumors (Stackpole et al 1963, Ein et al 1990, Ciftci et al 2001, Barontini et al 2006. Prevalence of hereditary and malignant tumors is controversial, but of utmost importance for quality-of-life considerations and survivorship (Ross 2000, Barontini et al 2006, De Krijger et al 2006, Pham et al 2006, King et al 2011. So far, no data from large population-based registries or long-term surveillance are available.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Children usually suffer from symptomatic and potentially life-threatening occurrence with bilateral and extraadrenal tumors (Stackpole et al 1963, Ein et al 1990, Ciftci et al 2001, Barontini et al 2006. Prevalence of hereditary and malignant tumors is controversial, but of utmost importance for quality-of-life considerations and survivorship (Ross 2000, Barontini et al 2006, De Krijger et al 2006, Pham et al 2006, King et al 2011. So far, no data from large population-based registries or long-term surveillance are available.…”
Section: Introductionmentioning
confidence: 99%
“…So far, no data from large population-based registries or long-term surveillance are available. Reports focused on pediatric patients are mostly based on few cases (Stackpole et al 1963, Kaufman et al 1983, Ein et al 1990, Ross 2000, Ciftci et al 2001, Barontini et al 2006, De Krijger et al 2006, Pham et al 2006, King et al 2011. Therefore, we sought to systematically perform molecular and clinical characterization of pediatric pheochromocytoma and paraganglioma to determine the long-term prognosis and outcomes in an international population-based registry.…”
Section: Introductionmentioning
confidence: 99%
“…PGL3 is mainly characterized by single HN-PGL (Schiavi et al 2005) but the occurrence of abdominal sPGL has also been reported (Mannelli et al 2007). PGL4 presents sPGL, which, at variance with tumors developed in PGL1 and PGL3, is malignant in more than 30% of cases, leading to metastatic disease (Linnoila et al 1990, Amar et al 2005, Pham et al 2006, Timmers et al 2007.…”
Section: Introductionmentioning
confidence: 99%
“…Estima-se uma taxa de recorrência de 1/100 casos (sendo mais de 40% destas recorrências correpondentes a casos de malignidade) [7,52]. Sendo assim, recomenda-se em todos os pacientes uma monitorização laboratorial anual (metanefrinas plasmáticas ou urinárias e cromogranina A) e com exames de imagem (ponderar a realização de ressonância magnética tóraco-abdomino-pélvica a cada um ou dois anos) [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25].…”
Section: /10unclassified
“…É um tumor raro na idade pediátrica, com uma prevalência estimada de 1:100.000 [6]. Na infância, a incidência de feocromocitoma é maior no sexo masculino, padrão que tende a reverter na adolescência, provavelmente devido às influências hormonais [7][8][9][10][11][12]. É comum a presença de síndromes familiares genéticas, autossômicas dominantes ou resultantes de mutações espontâneas, que aumentam a predisposição para o desenvolvimento de feocromocitomas, pela alteração do percursor da apoptose da célula neuronal simpá-tica [7,8,10,13].…”
Section: Introductionunclassified